Signaling and crosstalk of rhizobacterial and plant hormones that mediate abiotic stress tolerance in plants - Aloo, B. N.; Dessureault-Rompré, J.; Tripathi, V.; Nyongesa, B. O.; Were, B. A. (Frontiers in Microbiology, 2023)
Agricultural areas exhibiting numerous abiotic stressors, such as elevated water stress, temperatures, and salinity, have grown as a result of climate change. As such, abiotic stresses are some of the most pressing issues in contemporary agricultural production. Understanding plant responses to abiotic stressors is important for global food security, climate change adaptation, and improving crop resilience for sustainable agriculture, Over the decades, explorations have been made concerning plant tolerance to these environmental stresses. Plant growth-promoting rhizobacteria (PGPR) and their phytohormones are some of the players involved in developing resistance to abiotic stress in plants. Several studies have investigated the part of phytohormones in the ability of plants to withstand and adapt to non-living environmental factors, but very few have focused on rhizobacterial hormonal signaling and crosstalk that mediate abiotic stress tolerance in plants. The main objective of this review is to evaluate the functions of PGPR phytohormones in plant abiotic stress tolerance and outline the current research on rhizobacterial hormonal communication and crosstalk that govern plant abiotic stress responses. The review also includes the gene networks and regulation under diverse abiotic stressors. The review is important for understanding plant responses to abiotic stresses using PGPR phytohormones and hormonal signaling. It is envisaged that PGPR offer a useful approach to increasing plant tolerance to various abiotic stresses. However, further studies can reveal the unclear patterns of hormonal interactions between plants and rhizobacteria that mediate abiotic stress tolerance.